2017
DOI: 10.3389/fnagi.2017.00402
|View full text |Cite
|
Sign up to set email alerts
|

The “Aging Factor” Eotaxin-1 (CCL11) Is Detectable in Transfusion Blood Products and Increases with the Donor’s Age

Abstract: Background: High blood levels of the chemokine eotaxin-1 (CCL11) have recently been associated with aging and dementia, as well as impaired memory and learning in humans. Importantly, eotaxin-1 was shown to pass the blood-brain-barrier (BBB) and has been identified as crucial mediator of decreased neurogenesis and cognitive impairment in young mice after being surgically connected to the vessel system of old animals in a parabiosis model. It thus has to be assumed that differences in eotaxin-1 levels between b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…Importantly, CCL11 determinations for both cohorts were undertaken in the same laboratory, at the same time and with the origin of the samples blinded to the operator. Although the AMI subset had a much larger proportion of males than the 3C subset, CCL11 levels in plasma are not influenced by gender (Hoefer et al, 2017;Larsson et al, 2015). In contrast, CCL11 has been reported to be higher in older individuals (Bradburn et al, 2018;Shurin et al, 2007;Villeda et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…Importantly, CCL11 determinations for both cohorts were undertaken in the same laboratory, at the same time and with the origin of the samples blinded to the operator. Although the AMI subset had a much larger proportion of males than the 3C subset, CCL11 levels in plasma are not influenced by gender (Hoefer et al, 2017;Larsson et al, 2015). In contrast, CCL11 has been reported to be higher in older individuals (Bradburn et al, 2018;Shurin et al, 2007;Villeda et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…In contrast to this, we detected no significant differences in the protein concentration of MCP1 between old and young plasma samples. Next to MCP1, other factors like GDF11 or eotaxin (CCL11) are also discussed as age-dependent blood borne cytokines [35,[37][38][39]. These chemokines and cytokines were measured in moderate yet significantly higher abundances in young plasma samples compared to old plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…Further, IL24 could be found among the most significantly enriched transcripts after treatment with young serum with a log2fold change of +8.8 (Supplementary Table S1). The cytokines GDF11, MCP-1 and eotaxin were frequently discussed in rejuvenation experiments with old mice [34][35][36][37][38][39]. We therefore assessed the respective protein concentrations in old and young plasma samples via ELISA assays ( Figure S1C).…”
Section: Young Blood Serum Enhances Differential Global Gene Expressimentioning
confidence: 99%
“…Additionally, we observed that CCL11 and IL-4 had increased after 3 and 6 months of exposure to PM 1 in rats. CCL11 was shown to pass the BBB and was identified as a crucial mediator of decreased neurogenesis and increased cognitive impairment in mice [ 49 ]. Mice lacking IL-4 demonstrated cognitive impairment in a spatial learning task [ 50 ].…”
Section: Discussionmentioning
confidence: 99%